Diagnostic value of the rim sign on hepatobiliary scintigraphy - Shikare, Vinod Shekhar (World Journal of Nuclear Medicine, 2020)
The most commonly accepted pathophysiologic mechanism for the appearance of the “hot rim” sign is inflammatory changes from the gallbladder spreading to and affecting the surrounding liver. The “hot rim” sign has clinical relevance, because it is associated with a high incidence of perforated or gangrenous cholecystitis. The presence of these above-mentioned conditions increases the likelihood of complications and warrants urgent surgical evaluation. We present present the findings of on hepatobiliary scintigraphy and adjunct single-photon emission computed tomography/computed tomography-fused imaging in a case of acalculous cholecystitis, which has been confirmed on histopathology (marked degree of acute gangrenous cholecystitis).
Keywords: 99mTc-iminodiacetic acid scan; acalculous cholecystitis; rim sign; single-photon emission computed tomography/computed tomography